Improving oral and dental health through counseling to elementary school students in Jember - Ermawati, Tantin; Yani , Ristya Widi Endah; Syafriadi, Mei (Universitas Muhammadiyah Malang, 2021)
Measures to prevent dental and oral diseases in children can be done by providing information about parts of the teeth, dental caries and the process of dental caries, as well as plaque control as an effort to prevent the occurrence of dental and oral diseases. This activity was carried out aimed at increasing understanding and knowledge of the importance of maintaining oral health in children, especially elementary school students. The knowledge that has been given is expected to be able to change the behavior of students of SDN Kranjingan III Jember, East Java-Indonesia to be able to maintain the health of their teeth and mouth properly. This can be seen through the debris index. In addition to counseling activities, other methods provided were demonstrations of how to brush teeth, demonstration of pictures and posters carried out by the service team from the Faculty of Dentistry, University of Jember. The service activities carried out can increase knowledge and improve the degree of dental and oral health of SDN Kranjingan III Jember students.